Novel aspects of sialoglycan recognition by the Siglec-like domains of streptococcal SRR glycoproteins. (14th November 2016) - Bensing, Barbara A; Khedri, Zahra; Deng, Lingquan; Yu, Hai; Prakobphol, Akraporn; Fisher, Susan J; Chen, Xi; Iverson, Tina M; Varki, Ajit; Sullam, Paul M
Abstract: Serine-rich repeat glycoproteins are adhesins expressed by commensal and pathogenic Gram-positive bacteria. A subset of these adhesins, expressed by oral streptococci, binds sialylated glycans decorating human salivary mucin MG2/MUC7, and platelet glycoprotein GPIb. Specific sialoglycan targets were previously identified for the ligand-binding regions (BRs) of GspB and Hsa, two serine-rich repeat glycoproteins expressed by Streptococcus gordonii . While GspB selectively binds sialyl-T antigen, Hsa displays broader specificity. Here we examine the binding properties of four additional BRs from Streptococcus sanguinis or Streptococcus mitis and characterize the molecular determinants of ligand selectivity and affinity. Each BR has two domains that are essential for sialoglycan binding by GspB. One domain is structurally similar to the glycan-binding module of mammalian Siglecs (sialic acid-binding immunoglobulin-like lectins), including an arginine residue that is critical for glycan recognition, and that resides within a novel, conserved YTRY motif. Despite low sequence similarity to GspB, one of the BRs selectively binds sialyl-T antigen. Although the other three BRs are highly similar to Hsa, each displayed a unique ligand repertoire, including differential recognition of sialyl Lewis antigens and sulfated glycans. These differences in glycan selectivity were closely associated with differential binding to salivary and platelet glycoproteins. Specificity of sialoglycan adherence is likely an evolving trait that may influence the propensity of streptococci expressing Siglec-like adhesins to cause infective endocarditis.